Characteristics of forest honey from several areas in Riau Province, Indonesia - Sri Desfita; Wulan Sari; Yusmarini Yusmarini; Usman Pato; Grażyna Budryn (Hasanuddin University Food Science and Technology Study Program, 2022)
Honey quality is influenced by several factors, including transportation conditions and length of storage. This study aimed to investigate the composition, characteristics, and quality of honey from several regions in Riau and Riau honey sent to Java Island. Honey samples were obtained from five districts in Riau Province, namely, Inderagiri Hulu, Kuantan Singingi, Pelalawan, Bengkalis, and Kampar Regencies. The honey parameters observed were based on the Indonesia National Standard (SNI) of honey. Data were analyzed descriptively by comparing the characteristics of honey samples from Riau Province. Results showed a significant difference between honey sent and those not sent between islands. Significant differences were mainly observed in hydroxymethylfurfural (HMF) levels. Almost all honey samples sent to Java Island had HMF levels above 50 mg/kg. Meanwhile, all Riau honey samples from the five regions had HMF levels below 50 mg/kg. The diastase enzyme activity was slightly higher in the honey samples from the five regions. Land transportation to the island decreased the quality of honey as indicated by the high levels of HMF and decreased diastase enzyme activity. Therefore, mileage and storage conditions must be considered in the delivery of Riau honey to other regions.